The Effects of Background Music in a Simulated Initial Counselling Session with Female Subjects - Devlin, Hilton J.; Sawatzky, D. Donald (Canadian Journal of Counselling and Psychotherapy, 2011)
This study examined the effects of a background of soft, instrumental music, from the baroque era, on depth of client self-exploration, in counselling dyads. There were three levels of music: lively, slow, and no music. The subjects were twelve female undergraduates, and the counsellors were four final-year, graduate counselling students. Audiotapes of the sessions were analyzed, using the nine-point Depth of Client Self-Exploration Scale (Truax & Carkhuff, 1967). An analysis of Variance revealed significantly greater depth of client selfexploration (p ^.01) for both music conditions over the no music condition, and betweengroup t-tests indicated significantly greater depth of client self-exploration (p<.01) for the slow music condition over the lively music condition.